2022
DOI: 10.1186/s12906-022-03583-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antibiofilm, cytotoxic, and anti-acetylcholinesterase activities of Myrtus communis L. leaves essential oil

Abstract: Background The potential of essential oils (EOs) and of their principal constituents for eradication of biofilm and at the same time the research of new potential acetylcholinesterase inhibitors is gaining increasing interest in last years. The aims of this study were to determine the chemical composition and to evaluate the antibacterial, cytotoxic, and anti-acetylcholinesterase properties of Myrtus communis leaves essential oil and its main constituents. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 66 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…Oxides, such as 1,8-cineole (eucalyptol), are commonly found in Myrtus communis essential oil. Oxides can contribute to the expectorant and respiratory benefits of the essential oil and may have antimicrobial properties [ 112 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxides, such as 1,8-cineole (eucalyptol), are commonly found in Myrtus communis essential oil. Oxides can contribute to the expectorant and respiratory benefits of the essential oil and may have antimicrobial properties [ 112 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the anti-AChE, anti-BChE, anti-α-amylase, and anti-αglucosidase potential of other Eucalyptus EOs [7,16,[39][40][41][42], but no previous studies on the species examined here are present in the available literature. The presence of 1,8-cineole in our samples likely contributed to EO activity against acetylcholinesterase; in fact, in a previous work, an IC 50 of 13.5 µg/mL was reported for 1,8 cineole [42]. Moreover, 1,8 cineole displayed more robust inhibition against α-amylase, reducing enzyme activity by 43% at 75 µg/mL in comparison with α-glucosidase (IC 50 1 mg/mL) [16].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical profile of the myrtle EO revealed 32 volatile compounds (representing 83.2% of the total content) and was classified according to the chemical composition described by several authors [ 15 , 29 ]: terpenes represent 13.0%, of which 11.4% is monoterpenes and 1.4% is sesquiterpenes; terpenoids are about 68.0%, 17.5% is alcohols, 36.1% is esters, 13.7% is ethers, and 1.2% is aldehydes; lastly, phenylpropanoids represent 2.2% of the EO. Reviewing the literature, it is noticeable that there are two main standpoints on what the main constituents of myrtle EO are: those whose studies conclude that 1,8-cineole and α-pinene are the main constituents [ 16 , 18 , 31 , 33 ] and those whose studies point to myrtenyl [ 17 , 18 , 34 ]. Undoubtedly, it is possible to say that both are correct; whereas 1,8-cineole and α-pinene are predominant in Greece, Italy, France, and Algeria, myrtenyl acetate is prevalent in Portugal, Morocco, Spain, Tunisia, and Albania.…”
Section: Discussionmentioning
confidence: 99%
“…Myrtle EO can be classified into the cineoliferum type, rich in terpenes (α-pinene, limonene, and terpenoid oxides (1,8-cineole)), and the myrtenilacetatiferum type, rich in terpenic esters (terpenil acetate, linalyl-acetate, and bornyl-acetate) and terpenoid oxides (1,8-cineole) [ 16 ]. It is characterized by a pleasant aroma and taste, in which α-pinene, 1,8-cineole, limonene, myrtenyl acetate, and myrtenol are the main contributors [ 17 , 18 ]. Myrtle properties represent an added value at an industrial level, as they have been shown to have antimicrobial and antioxidant activities [ 17 ].…”
Section: Introductionmentioning
confidence: 99%